Propagation of Casuarina equisetifolia Forst, by Planting Shoots - Somasundaram, T. R.; Jagadees, S. Stanley (Indian Forester, 1977)
Casuarina equisetifolia Forst, is normally propagated through seeds. Vegetative propagation through air layers and suckers are also known. In this paper a new method of propagation by planting lateral or side shoots has been described. Best results were achieved by tbe use of rooting hormone, Seradix 2, a proprietory product of May & Baker.